Internalisasi Norma Hukum Sebagai Model Institusional Perilaku Sosial Masyarakat - Niki Arthur (Perkara : Jurnal Ilmu Hukum dan Politik, 2025)
This study investigates the institutional mechanisms through which legal norms are internalized and transformed into social behavior in Indonesian society. Using a qualitative exploratory–descriptive approach, data were collected through in-depth interviews, observation, and document analysis across three sociocultural settings. The findings reveal that internalization is not merely the result of formal enforcement or legal sanctions, but emerges through a layered social process involving translation of legal values by institutional actors such as community leaders, educators, and local organizations. Legal norms become effective when they are repeatedly enacted in everyday practices and perceived as socially relevant, ultimately forming behavioral orientations that operate without coercion. The study contributes a conceptual institutional model that integrates normative, institutional, and sociological dimensions and offers practical implications for policymakers to design ecosystem-based internalization strategies. Limitations include a limited number of research sites and the absence of standardized quantitative measures, suggesting the need for future mixed-methods studies to broaden applicability.